Indigenous communities and marine mammal tourism management: incorporating the perspectives of the indigenous Māori people of Aotearoa/New Zealand - Elmahdy, Yasmine M.; Orams, Mark; Lück, Michael; Schänzel, Heike (Frontiers in Sustainable Tourism, 2025)
IntroductionMany coastal and island indigenous people have long-standing important relationships with marine mammals. In many cases whales and dolphins have been viewed as spiritual beings with strong connections to indigenous people's histories, and connections to the world around them. In other cases, they have been viewed as important guides and symbols that form parts of creation stories, art, music and important cultural practices. For indigenous Māori in Aotearoa/New Zealand whales have a significance as cultural “taonga” (treasure) and the relationship between whales and Māori are deep and entwined with understanding and connection to the Pacific Ocean and the Pacific islands. Aotearoa/New Zealand's Marine Mammals Protection Act formally recognizes this relationship and is considered world-leading in its incorporation of indigenous Māori rights with regard to marine mammals alongside of the strong focus on marine mammal conservation. This legislative regime sits within the context of increasing evidence from New Zealand and elsewhere that shows that the current growth patterns and intensity of marine tourism activities can have adverse short- and long-term impacts on marine mammals. Consequently, there is a tension between the ambitions to protect marine mammals and include indigenous Māori's important relationship with marine mammals and the risks associated with the growth of marine mammal tourism.MethodsThis qualitative study uses a case study approach to explore Aotearoa/New Zealand's indigenous Māori people's connection with marine mammals and their role in marine mammal tourism management. Data were obtained through semi-structured, in-depth interviews with Māori participants directly involved in marine mammal conservation and tourism management.Results and discussionThe findings show a strong historical, spiritual, and cultural connection between indigenous Māori and marine mammals. Recommendations for improving marine mammal tourism policy and management include greater engagement of indigenous communities in conservation efforts and incorporating Māori traditional ecological knowledge and perspectives into marine mammal tourism management. The study emphasizes the importance of intergenerational decision-making in natural resource management, with a particular focus on marine mammal tourism. The study contributes to the broader understanding of indigenous Māori's relationship with nature and tourism, particularly how indigenous people's perspectives can inform marine mammal conservation and tourism management.